A22 Hypothalamic changes in Huntington's disease. (16th November 2010) - van Wamelen, D; Aziz, A; Shan, L; Anink, J; Roos, R A C; Swaab, D
Abstract : Background: In recent years it has become increasingly clear that the hypothalamus might be affected in Huntington's disease (HD), and that this may underlie many features in this disease. Research on the hypothalamus itself in HD patients, however, has so far been limited. Aims: To systematically assess four major hypothalamic nuclei, the suprachiasmatic (SCN), paraventricular (PVN), infundibular (INF) and tuberomamillary nucleus (TMN) for changes in the level of neurotransmitters/neuromodulators in these nuclei. Methods: We used a combination of quantitative immunohistochemistry and radioactive in situ hybridisation techniques on post-mortem, paraffin embedded, hypothalamic tissue in HD patients (n=9) and well matched control subjects (n=9). Results: In the SCN, the number of vasopressin and vasoactive intestinal polypeptide expressing neurons was decreased in HD patients (p=0.03 and 0.001, respectively). Numbers of melatonin 2 receptor expressing neurons were unchanged (p=0.32). In the PVN, the number of corticotropin releasing hormone expressing neurons was unchanged (p=0.55), as were thyroid stimulating hormone mRNA levels (p=0.21). In the INF, the number of neuropeptide Y expressing neurons was decreased in HD patients (p=0.01), the number of neurons expressing α-melanocyte stimulating hormone, agouti related peptide and cocaine and amphetamine regulated transcript was unchanged (p=0.20, p=0.32 and p=0.20, respectively). In the TMN, mRNA levels of histidine decarboxylase, the rate limiting enzyme for histamine production, were increased in HD patients (p=0.05). Conclusions: These results show that the hypothalamus in HD is severely affected, contributing to several features in patients, such as circadian rhythm disturbances, weight loss and cognitive decline. Furthermore, our findings may provide a basis for rational therapeutic strategies aimed at ameliorating these symptoms.